MENGATASI MISKONSEPSI SISWA MELALUI STRATEGI KONFLIK KOGNITIF DI SEKOLAH MENENGAH PERTAMA - Muhamat Hidayatul Ridho; Zubaidah Zubaidah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aimed to describe students' misconceptions on the subject of Pythagorean theorem before and after being resolved using cognitive conflict strategies in SMP Negeri 2 Pontianak. The method used is a qualitative descriptive with the form of a case study. The subjects in this research is 6 students from grade VIII of SMP Negeri 2 Pontianak in the academic year 2019/2020. While the data technique used is a test technique with a instrument in the form of a diagnostic test. The misconceptions revealed by the researchers based on the pre-test results were errors in using the term italic, using formulas that were not in accordance with the information in the questions, wrong in determining the conditions for the application of the Pythagorean theorem, errors in completing exponent calculations, and errors in determining the conditions for the formation of acute or obtuse triangles. . Based on the results of research and data analysis in this research, it is shown that cognitive conflict can overcome students' misconceptions on the subject of the Pythagorean theorem which can be seen in the student post-test results that show the application of concepts and the application of proper procedures in solving questions. Keywords: Cognitive Conflict Strategy, Misconception, Pyhtagorean Theorem